The student response on the use of renewable energy graphical interface simulator in learning environment - Gopabala Krishnan, Lavaniya; Albani, Aliashim; Segar, Yogesswary; Ridzuan, Abdul Rahim; Ismail, Mohd Khairi; Musa, Mohd Azlan; Gunaseelan, Khemaalatha; Subramaniam, Tamil Selvan; Ibrahim, Mohd Zamri (Frontiers in Education, 2023)
Introduction The purpose of this study is to evaluate students’ responses regarding the usefulness of a graphical user interface (GUI) tool in the context of their respective learning environments. The Energy Computator GUI (EC-GUI) helps to simplify the STEM student’s learning processes. The EC-GUI serves as a simulator that can assist in computing formulas, designing graphs, acting as a unit converter, and automatically deriving parameters. Methodology Furthermore, a survey, which included closed and open questions, was carried out on a selection of students majoring in STEM subjects at Universiti Malaysia Terengganu (UMT) who were enrolled in the Renewable Energy course. A total of 54 respondents participated in the survey and 90.8% of them expressed satisfaction with the EC-GUI provided. The research involved using two distinct kinds of analysis: a parametric analysis, the paired sample t-test, and a non-parametric analysis, the Wilcoxon signed-rank test. Results The study findings indicated that the majority of the respondents felt that the difficulty level of the subjects did not change after using the EC-GUI. However, it helped to simplify the learning process for students in STEM fields. The p-value of the appropriate teaching aid tool was less than 0.05, indicating that the results were significant both before and after using the EC-GUI. Conclusion The study suggests that a similar GUI tool could be implemented in Malaysia’s teaching and learning processes as it is easy to build and use.